Cataract and myotonic dystrophy: the role of molecular diagnosis. Issue 9 (September 1993) - Reardon, W; MacMillan, J C; Myring, J; Harley, H G; Rundle, S A; Beck, L; Harper, P S; Shaw, D J
Abstract : Myotonic dystrophy (dystrophia myotonica), the commonest and most variable of the muscular dystrophies of adult life, has long been known to be associated with cataract, while slit-lamp examination for specific lens opacities has been one of the principal methods of presymptomatic detection of gene carriers. The recent discovery that the myotonic dystrophy mutation is an unstable DNA sequence, composed of varying numbers of CTG triplet repeats, now allows a specific molecular test for this disorder, as well as explaining the phenomenon of anticipation. A series of case reports is presented to illustrate the important practical applications of this development in relation to ophthalmic aspects of the disorder. Reassessment of the specificity of the ophthalmic changes may be required and it will be important for molecular analysis to be used alongside ophthalmic studies, when determining whether family members carry the mutation for myotonic dystrophy.